Desenvolvimento e validação do questionário de prontidão para o esporte com foco nas lesões musculoesqueléticas - Silveira Júnior, José Antonio da (2016)
Sports injuries are disorders that have great impact on the athletes’ performance. The present research aimed to develop and validate a pre-participation questionnaire that identifies athletes with probable musculoskeletal injuries or risk factors for the purpose of select them for specialized medical evaluation. The Delphi Technique was applied, which consists of gathering information and arriving at experts’ consensus about a specific subject that is well not known in the literature. The initial version of the Musculoskeletal Injuries Readiness Questionnarie (MIR-Q) was based on the researcher’s experience in the fields of sportive orthopedic/traumatology and exercise and sport medicine (ESM), and was sustained by theoretical references. In the pilot phase, an analysis of the MIR-Q’s initial content was performed by nine specialists in ESM. In this phase, question 5 was eliminated from the seven previous questions. In the first round of Delphi Technic, 25 experts evaluated the remained six questions of MIR-Q. The rounds were programmed to be repeated until the minimum percentage of convergence of opinion (75%) was reached among most of the specialists (higher than 50%) for each question, based on Likert-type scale of agreement of 1 to 5. In round 1, three questions were modified and the feedback revealed an agreement level ranging from 80 to 100%). The MIR-Q’s internal consistence (Cronbrach’ α) showed satisfactory levels at the first round (0,70) . Thus, the present questionnaire proved to be a simple and valid tool, from the point of view of content validity, for screening athletes with probable musculoskeletal injuries for referral to specialists.